Design and Analysis of Authenticated Encryption Modes - Bhattacharjee, Arghya (Kolkata: Indian Statistical Institute, 2024)
This thesis proposes and analyses the security of a few symmetric key modes. The first three of them are NAEAD modes, named Oribatida, ISAP+ and OCB+. Oribatida is lightweight, sponge-based, INT-RUP secure and achieves better than the default PRF security of a keyed sponge. ISAP+ is an instance of a generic EtHM involving a PRF and a hash, a generalisation of ISAP-type modes. The generic sponge hash of ISAP is replaced with a feed-forward variant of it in ISAP+, which results in better security. OCB+ uses OTBC-3 (a nonce-respecting BBB secure offset-based tweakable block-cipher) in an OCB-like mode to achieve BBB privacy. We conclude with a BBB secure NE mode named CENCPP*, which is a public permutation-based variant of the block-cipher-based mode CENC as well as a variable output length version of SoEM. All the relevant security proofs have been done using a method named Coefficients H Technique.
Preliminaries -- Oribatida -- ISAP+ -- OCB+ -- CENCPP*
Thesis (Ph.D.)- Indian statistical Institute, 2024
Includes references
Guided by Prof. Mridul Nandi